Age and choice in health insurance: Evidence from Switzerland - Karolin Becker; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2007)
Elements of regulation inherent in most social health insurance systems are a uniform package of benefits and uniform cost sharing. Both elements risk to burden the population with a welfare loss if preferences differ. This suggests introducing more contracted choice; however, it is widely believed that this would not benefit the aged. This study examines the relationship between age and willingness-to-pay (WTP) for additional options in Swiss social health insurance. Through discrete choice experiments (DCE), a marked diversity of preferences can be established. The findings suggest that while the aged do exhibit more status quo bias, they require less rather than more specific compensation for selected cutbacks considered, pointing to potential for contracts that induce self-rationing in return for lower premiums.
Keywords: C35; C93; D61; I11; I18; 330; willingness-to-pay; health insurance; age; rationing; Willingness to pay; Gesetzliche Krankenversicherung; Altersgruppe; Test; Schweiz; Diskrete Entscheidung